Distribution of long chain heterocyst glycolipids in n2-fixing cyanobacteria of the order stigonematales - Bauersachs, T.; Mudimu, O.; Schulz, R.; Schwark, Lorenz (Pergamon, 2014)
N2-fixing heterocystous cyanobacteria have been shown to hold a suite of unique glycolipids, so-called heterocyst glycolipids (HGs), as part of the heterocyst cell envelope. It was also demonstrated that the distribution of these components bears a high level of chemotaxonomic information, which allows distinguishing heterocystous cyanobacteria of the order Nostocales on a family or even genus level. Here we report the heterocyst glycolipid composition of five representatives of the order Stigonematales (Fischerella muscicola, Fischerella sp., Nostochopsis lobatus, Westiellopsis prolifica and Westiellopsis sp.), which have largely escaped a detailed investigation of their HG content so far. All analyzed strains contained a similar qualitative mixture of HGs with 1-(O-hexose)-3,29,31-dotriacontanetriol (HG32 triol) dominating over minor quantities of 1-(O-hexose)-29-keto-3,31-dotriacontanediol (HG32 keto-diol). When viewed in conjunction with previous culture studies on the HG composition of heterocystous cyanobacteria, our results demonstrate that HG32 triols and their corresponding keto-diol varieties are characteristic biological markers for heterocystous cyanobacteria of the order Stigonematales. Given that these N2-fixers primarily occur in tropical to subtropical freshwater lakes and subaerial habitats, the presence of HG32 triols and keto-diols in sedimentary sequences may offer additional information on climatic conditions in palaeoenvironmental studies.